The effect of a ban on gender-based pricing on risk selection in the German health insurance market - Shan Huang; Martin Salm (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Starting from December 2012, insurers in the European Union were prohibited from charging gender-discriminatory prices. We examine the effect of this unisex mandate on risk segmentation in the German health insurance market. While gender used to be a pricing factor in Germany's private health insurance (PHI) sector, it was never used as a pricing factor in the social health insurance (SHI) sector. The unisex mandate makes PHI relatively more attractive for women and less attractive for men. Based on data from the SOEP we analyze how the unisex mandate affects the difference between women and men in switching rates between SHI and PHI. We find that the unisex mandate increases the probability of switching from SHI to PHI for women relative to men. This effect is strongest for self-employed individuals and mini-jobbers. On the other hand, the unisex mandate had no effect on the gender difference in switching rates from PHI to SHI. Because women have on average higher health care expenditures than men, our results imply a reduction of advantageous selection into PHI. Our results demonstrate that regulatory measures such as the unisex mandate can reduce risk selection between public and private health insurance sectors.
Keywords: I13; D82; H51; 330; unisex mandate; public and private health insurance; risk selection; Germany